2010
DOI: 10.1017/s1751731110000790
|View full text |Cite
|
Sign up to set email alerts
|

Resource use efficiency in urban and peri-urban sheep, goat and cattle enterprises

Abstract: Urban livestock husbandry receives growing attention given the increasing urban demand for livestock products. At the same time, little is known about the resource use efficiency in urban livestock enterprises and eventual negative externalities. In livestock production, feeds are an important resource whose nutrients are transformed into products (meat and milk) to generate financial return to the producer. The lack of knowledge on nutrient supply through feed might lead to oversupply with severe environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 35 publications
1
9
1
Order By: Relevance
“…While the major constraints of the system were identified as limited availability and high prices of feed resources (Schiere and van der Hoek, 2001;Thys et al, 2005), a study by Diogo et al (2010) in Niamey (Niger) revealed that farmers operating in this system provide excessive feed and nutrients to their animals.…”
Section: Cattle Farming Systemsmentioning
confidence: 99%
“…While the major constraints of the system were identified as limited availability and high prices of feed resources (Schiere and van der Hoek, 2001;Thys et al, 2005), a study by Diogo et al (2010) in Niamey (Niger) revealed that farmers operating in this system provide excessive feed and nutrients to their animals.…”
Section: Cattle Farming Systemsmentioning
confidence: 99%
“…2005; Graefe et al 2008; De Bon et al 2010; Diogo et al . 2010, Predotova et al 2010). It has also been widely argued in the general UPA literature and in several case studies that urban farmers are among the poorest of poor urban dwellers who have no other livelihood alternatives (Lado 1990; Rogerson 1993; Enete and Achike 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, the two species have not received equal attention in studies on urban small ruminant production in the West African context. Respective studies (Siegmund-Schultze and Rischkowsky 2001; Touré and Ouattara 2001; Killanga et al 2004; Rischkowsky et al 2006; Diogo et al 2010), which are limited in number, mainly focused on sheep, neglecting goats. They are also limited in their scope: some to just the socio-economic characteristics of the keepers, most to one city, others to the management practices and flock productivity, providing therefore a patchwork view of the prevailing production systems.…”
Section: Introductionmentioning
confidence: 99%